Fault Tolerance in Heterogeneous Automotive Real-time Systems - Lex, Johannes; Margull, Ulrich; Fey, Dietmar; Mader, Ralph (Informatik aktuell, 2022)
Recent developments in the area of autonomous driving lead to an exponential growth of software complexity in the automotive industry. To cope with those increasing demands on computational power and software architectures, new developments in the area of electronic control units (ECU) emerged, like the ability to partition AUTomotive Open System ARchitecture (AUTOSAR) Classic Software with Software Clusters (SWCL) and the introduction of embedded high performance computers in the Electric-/Electronic-Architecture (E-/E-Architecture). At the same time the demand for high availability of critical functionalities rises with the degree of automatization. This paper presents a new flexible and resource-saving fail operational strategy, which increases the availability of a system by instrumenting SWCL and embedded high performance computers.<br
CRIS-Team Scopus Importer:2022-06-24